2022
DOI: 10.1186/s12885-022-09989-0
|View full text |Cite
|
Sign up to set email alerts
|

CTNNB1 mutations, TERT polymorphism and CD8+ cell densities in resected hepatocellular carcinoma are associated with longer time to recurrence

Abstract: Background Hepatocellular carcinoma (HCC) is a fatal disease characterized by early genetic alterations in telomerase reverse transcriptase promoter (TERTp) and β-catenin (CTNNB1) genes and immune cell activation in the tumor microenvironment. As a novel approach, we wanted to assess patient survival influenced by combined presence of mutations and densities of CD8+ cytotoxic T cells. Methods Tissue samples were obtained from 67 HCC patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The lack of association between the C variant and survival is unclear, but the heterogeneity of second-line therapies and re-surgery at relapse might likely have impacted on this correlation. Our association of the C variant of rs2853669 with a favorable patient outcome is in agreement with prognostic data from other cancer types 35 , 36 and likely depends on the destroying effect of the C allele on a pre-existing binding site for ETS transcription factors on TERT promoter, resulting in reduced TERT expression. 15 Nevertheless, even opposite results, with the C allele associated with a worse prognosis, have been reported.…”
Section: Discussionsupporting
confidence: 88%
“…The lack of association between the C variant and survival is unclear, but the heterogeneity of second-line therapies and re-surgery at relapse might likely have impacted on this correlation. Our association of the C variant of rs2853669 with a favorable patient outcome is in agreement with prognostic data from other cancer types 35 , 36 and likely depends on the destroying effect of the C allele on a pre-existing binding site for ETS transcription factors on TERT promoter, resulting in reduced TERT expression. 15 Nevertheless, even opposite results, with the C allele associated with a worse prognosis, have been reported.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, CTNNB1 was also found to be closely related to a variety of tumor diseases such as liver cancer, gastrointestinal carcinoma and endometrial carcinoma (Ambrozkiewicz et al, 2022;Chao et al, 2022). Although few direct studies have shown the correlation between CTNNB1 and IH.…”
Section: Alternative Splicing Results In Multiple Transcript Variantsmentioning
confidence: 99%
“…Recently, Duan X et al found that FOXC1A can regulate vascular integrity and brain vascular development through targeting CTNNB1 ( Duan et al, 2022 ). In addition, CTNNB1 was also found to be closely related to a variety of tumor diseases such as liver cancer, gastrointestinal carcinoma and endometrial carcinoma ( Ambrozkiewicz et al, 2022 ; Chao et al, 2022 ). Although few direct studies have shown the correlation between CTNNB1 and IH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to assessing for the presence of ctDNA, liquid biopsy can identify specific genes that predict patient outcomes based on cancer. For example, in HCC, CTNNB1 and TERT have been shown to be two of the most commonly mutated genes and were present frequently in our cohort [ 33 ]. The presence of these two mutations, along with a mutation in TP53 , in post-operative ctDNA has been associated with a decreased recurrence-free survival [ 30 ].…”
Section: Discussionmentioning
confidence: 99%